Production of Activated Carbon from High-Grade Bituminous Coal to Removal Cr (VI) - Esthi Kusdarini; Denis Rocky Pradana; Agus Budianto (Reaktor, 2022)
Activated carbon was produced from high-grade bituminous coal, potentially removing Cr metal in textile industrial waste. The purposes of this study were 1) getting activated carbon characteristics, 2) studying the impact of reagent concentration and activation temperature on the activated carbon characteristics, and 3) getting the isotherm adsorption equation for activated carbon developed by Freundlich and Langmuir on Cr metal. This research used an experimental method with a laboratory scale, which means the manufacture of activated carbon and a test of adsorbs power of activated carbon to the Cr metal were conducted in the laboratory. Activated carbon manufacture through carbonization process of chemical activation used reagent (NH4)3PO4, neutralization, filtration, physical activation, and cooling. At the same time, it tested the adsorption power of the activated carbon to Cr metal through activated carbon contact with a solution containing some Cr6+ ion. The update in this research was using reagent (NH4)3PO4 and the test of adsorption power of activated carbon to Cr6+ ion contained in the artificial waste. This research showed activated carbon that has been activated using reagent (NH4)3PO4 0.5 – 2 M at physical activation temperature of 825oC and has met the standard of SNI number 06-3730-1995. The best-activated carbon was produced from chemical activation using (NH4)3PO4 1 M solution and physical activation at 825oC. The best-activated carbon characteristics contained 1.27% water; 17.17% content of volatile matter, 9.39% was ash content; 73.17% contained fixed carbon, and the iodine value was 1248.30 mg/g. The best Equation of Langmuir isotherm adsorption of activated carbon to the Cr6+ produced Constant Ar = -90.0901 and Kc = -0.0075.